Overview of strategies for writing case report as medical education - Yosuke Kakisaka; Franchesca Gabriel (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Physicians have at least two roles as medical professionals: direct patient management, which involves diagnosis and treatment, and delivering new discoveries acquired from daily clinical activities to patients both in the present and future world. Importantly, these two activities are closely related, and the process of case report writing will integrate them [1]. Here we introduce several activities which will be helpful for case writing.